Genetic diversity in accessions of lima bean (Phaseolus lunatus L.) determined from agro-morphological descriptors and SSR markers for use in breeding programs in Brazil - de Jesus Pires C. (2022)
© 2021, The Author(s), under exclusive licence to Springer Nature B.V.Lima bean (Phaseolus lunatus L.) have high genetic diversity, especially in Brazil, which has been maintained both on farms and in germplasm banks. Knowledge of the genetic diversity of germplasm in landraces is important for the development of breeding programs. We investigated the genetic diversity of lima bean landraces accessed in the Phaseolus Germplasm Bank of the Federal University of Piauí (PGB-UFPI, Brazil), using agro-morphological and microsatellite markers (SSRs). We analyzed 26 qualitative and 11 quantitative traits, following the Bioversity International descriptors. Furthermore, 15 SSRs were used to determine the genetic polymorphism and genetic differentiation among genotypes. The agro-morphological traits and SSR markers were reliable and effective for determining the genetic diversity of the accessions. Cluster analysis revealed a considerable phenotypic diversity among the accessions for some characters related to agronomic performance, such as the number of pods per plant, number of seeds per pod, and weight of 100 seeds. At the molecular level, ten loci showed polymorphism; the number of alleles per locus varied from two to seven, with mean polymorphism information content of 0.282 per locus. Loci GATS91 and PVat001 were highly informative and are indicated for further studies of lima bean. The accessions constitute an important gene pool for future breeding programs, especially accession UFPI-262. Accessions UFPI-262 and UFPI-252 can be used in crosses, as they are genetically distant and complementary in their characteristics.